A Matter of Light : Nine Photographers in the Vatican Museums - Forti, Micol; Mauro, Alessandra (Rome ; Città del Vaticano : Contrasto : Edizioni Musei Vaticani, 2018)
Armstrong, Bill ; Bialobrzeski, Peter ; Biasiucci, Antonio ; Fleischer, Alain ; Jodice, Francesco ; Jodice, Mimmo ; Kawauchi, Rinko ; Parr, Martin ; Siragusa, Massimo
boek